PsycEXTRA Dataset 2007
DOI: 10.1037/e703392007-001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Recent Stressful Experiences on HIV-Risk-Related Behaviors

Abstract: Limited research has captured the wide varieties of distinct, but interrelated, life stressors that young men who have sex with men (YMSM) experience as emerging adults. We examined the way recent experiences of a diverse set of stressors predict illicit drug use, alcohol misuse, and inconsistent condom use (i.e., unprotected anal intercourse) among an ethnically diverse cohort of YMSM (N=526). Results indicated that stress related to financial and health concerns were associated with increased risk for substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The results also are supported by our prior finding that stressful life events were a risk factor for HIV seroconversion among Polaris participants, likely via mediation through its effect on sexual risk behavior [38]. Other studies have observed a relation between UAI and stress [29][30][31][32] or other psychosocial health problems [12].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results also are supported by our prior finding that stressful life events were a risk factor for HIV seroconversion among Polaris participants, likely via mediation through its effect on sexual risk behavior [38]. Other studies have observed a relation between UAI and stress [29][30][31][32] or other psychosocial health problems [12].…”
Section: Discussionsupporting
confidence: 86%
“…A few studies have found that stressors associated with poverty were associated with HIV risk behaviors among non-MSM samples [24][25][26][27]. Among MSM, findings have been mixed, with one study finding no associations [28], and other studies finding inconsistent associations with some stressors, such as victimization, but not others (e.g., poverty-related stressors) [29][30][31][32]. Most of the studies on stress and UAI are limited by their smaller sample size and the use of cross-sectional designs that cannot assess whether the stressful events temporally preceded UAI.…”
Section: Introductionmentioning
confidence: 98%
“…Other studies, however, have found that social support from family or friends was not significantly associated with HIV sexual risk behavior among Black (Garofalo et al, 2010;Jones, Johnson, et al, 2008) or Latino YMSM (Garofalo et al, 2010). Similarly, Wong, Kipke, Weiss, and McDavitt (2010) did not find that there was a significant relationship between social support and HIV sexual risk behavior among YMSM, although these findings were not reported for racial subgroups of YMSM.…”
Section: Cultural Factorsmentioning
confidence: 77%
“…Garofalo and colleagues (2010) found that internalized homophobia was not significantly associated with HIV sexual risk behavior among Black or Latino YMSM. Other studies of YMSM that did not examine this relationship specifically among Black or Latino YMSM were mixed in terms of yielding significant Rosario et al, 2006;Waldo et al, 2000) and nonsignficant findings (Dudley et al, 2004;Wong et al, 2010). Jones and colleagues (2008) found that discrimination based on race or sexual orientation or experiencing disapproval from a minister or priest because of sex with men was not significantly related to HIV sexual risk behavior among Black YMSM.…”
Section: Cultural Factorsmentioning
confidence: 93%
“…Second, social exclusion reinforces YMSM invisibility in society, and creates the impression that loneliness and poor mental health may be the byproduct of social exclusion (Leary, 1990). Increasing evidence points to the link among social exclusion, poor mental health, and HIV risk among YMSM (Natale, 2009;Wong, Kipke, Weiss, & McDavitt, 2010). Therefore, HIV risk taking among YMSM may serve as an outlet to build connection with others.…”
Section: Discussionmentioning
confidence: 92%